'As long as he's coming home to me': vulnerability, jealousy and violence in young people's relationships in remote, rural and regional Australia. Issue 2 (4th May 2017) - Senior, Kate; Helmer, Janet; Chenhall, Richard
ABSTRACT: Drawn from a sample of 88 Indigenous young people in five locations in urban and remote Northern Australia, this research utilised a combination of qualitative approaches to encourage young people to discuss their ideas about sexual relationships and violence. Indigenous youth discussed highly public displays of violence, as well as violence within intimate settings and the interrelationships between these two arenas. A key finding of this research was that young people described violence as an accepted part of their sexual relationships and this normalisation led to significant tensions in their experiences and management of their everyday relationships. While violence around young people's relationships in remote communities was reported to some extent as being controlled through both the public and controlled form they take, we found that the increasing mobility of young people from remote to urban locations due to education opportunities and the impact of social media can lead to more serious forms of violence and tension in the maintenance of young people's sexual relationships. This contributes new findings to the literature on Indigenous young people's experiences in relationship forming and management, an area that has received little attention in the academic literature.